Guidelines for Maxillary Incisal Edge PositionÃƒÂ¢Ã¢â€šÂ¬Ã¢â‚¬ÂA Pilot Study: The Key Is the Canine - Carl E. Misch, DDS, MDS (Journal of Prosthodontics, 2008)
The purpose of this pilot study was to evaluate the relationship between the vertical position of the maxillary central incisal edge and the maxillary canine relative to the maxillary lip line in repose of dentate patients